Proceedings of the 2020 ACM Conference on Innovation and Technology in Computer Science Education 2020
DOI: 10.1145/3341525.3387418
|View full text |Cite
|
Sign up to set email alerts
|

An International Pilot Study of K-12 Teachers' Computer Science Self-Esteem

Abstract: Computer Science (CS) is a new subject area for many K-12 teachers around the world, requiring new disciplinary knowledge and skills. Teacher social-behavioral factors (e.g. self-esteem) have been found to impact learning and teaching, and a key part of CS curriculum implementation will need to ensure teachers feel confident to deliver CS. However, studies about CS teacher self-esteem are lacking. This paper presents an analysis of publicly available data (n=219) from a pilot study using a Teacher CS Self-Este… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…This could support teachers regarding the frequently identified lack of time for planning and during computer science lessons [40,50], as for example reported in a recent study on the efficiency of automated hints for debugging Scratch programs [15]. Apart from timing issues, automated tools might also provide some support regarding the reported relatively low computer science self-esteem [47] and programming self-concept [13] of primary school teachers as "it is not only shown what is wrong or messy, but also what you have done well. That is motivating" (Trmt, P64) (i.e., it reports code perfumes [34]).…”
Section: Advantages For Teachersmentioning
confidence: 59%
“…This could support teachers regarding the frequently identified lack of time for planning and during computer science lessons [40,50], as for example reported in a recent study on the efficiency of automated hints for debugging Scratch programs [15]. Apart from timing issues, automated tools might also provide some support regarding the reported relatively low computer science self-esteem [47] and programming self-concept [13] of primary school teachers as "it is not only shown what is wrong or messy, but also what you have done well. That is motivating" (Trmt, P64) (i.e., it reports code perfumes [34]).…”
Section: Advantages For Teachersmentioning
confidence: 59%
“…. These initial findings suggest a pressing need for future research to look further into teacher CS self-esteem to inform..." [29]. No replication studies were identified.…”
Section: Data Extraction and Mapping Of Studiesmentioning
confidence: 99%
“…The research that is carried out can be in different phases. It may be research that aims to inform the design of PD interventions and programs [29]. Results from such studies can be used later when designing and implementing an intervention.…”
Section: Motivation Research Questions and Scopingmentioning
confidence: 99%